Effective properties of flexoelectric fiber-reinforced nanocomposite. (December 2018) - Sidhardh, Sai; Ray, M.C.
Graphical abstract: Highlights: A novel flexoelectric fiber reinforced composite (FLFRC) has been proposed. The effective electro-mechanical properties of FLFRC have been evaluated analytically. Tailoring of the FLFRC to obtain superior coupling coefficients in comparison to the monolithic dielectric has been demonstrated. Interesting properties like negative flexoelectric coefficients for the FLFRC have been observed. Abstract: The effective flexoelectric coefficients of a multifunctional flexoelectric fiber reinforced composite (FLFRC) have been estimated using an analytical micromechanics based model. The analytical estimation carried out here has been validated with the effective piezoelectric and the fourth-order elastic constants of the composite available in literature. The effective flexoelectric coefficients of the composite show a size-dependent effect, not seen in similar calculations for piezoelectric composites. Also, above a critical fiber volume fraction with a suitable choice of matrix, the effective flexoelectric properties of the FLFRC can be tailored to be significantly superior to those of the monolithic dielectric solid. It is noted that, the FLFRC can be customized to have negative axial flexoelectric coefficients. This study opens new avenues for further research on developing smart nanocomposites characterized with enhanced functional properties.